Mechanical nociceptive assessment of the equine hoof following distal interphalangeal joint intra-articular anesthesia - Malacarne, Bruno D.; Cota, Leticia O.; Neto, Antônio C.P.; Paz, Cahuê F.R.; Dias, Lucas A.; Corrêa, Mayara G.; Carvalho, Armando M.; Faleiros, Rafael R.; Xavier, Andressa B.S. (PeerJ, 2020)
Background With the hypothesis that equine dorsal lamellar tissue can be desensitized by anesthesia injection into distal interphalangeal joint (DIPJ), the objective was to assess the mechanical nociceptive threshold of hoof dorsal lamellae following intra-articular (IA) administration of lidocaine into this joint. Methods The DIPJ of the forelimbs of six adult healthy horses were injected with either 5 mL of lidocaine, or 5 mL of lactated Ringer’s solution. Treatments were randomly distributed, with each forelimb undergoing a single treatment. The hooves were evaluated pre- and post-injection at pre-selected times over 4 h, using a pressure algometry model. Mechanical nociceptive thresholds (MNTs) were recorded for the sole (dorsal, palmarolateral, and palmaromedial regions), coronary band (medial, lateral, and dorsal regions), heel bulbs (medial and lateral), and dorsal lamellar region (2 cm and 4 cm distal to the coronary band). The MNT means were compared over time using the Friedman test and between treatments using the Wilcoxon signed-rank test, with values of P < 0.05 considered statistically significant. Results There were no differences between treatments for any region of the hoof during the evaluation period. However, MNT values indicating analgesia were recorded in the dorsal lamellar region in 50% of hooves following adminstration of lidocaine into the DIPJ. Conclusion The administration of 5 mL of lidocaine into the DIPJ does not significantly increase the mechanical nociceptive threshold of the equine hoof.
Keywords: Analgesia; Diagnostic; Lameness; Pain; Pressure algometry